2016
DOI: 10.1007/s10637-016-0403-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1b study of orteronel in postmenopausal women with hormone-receptor positive (HR+) metastatic breast cancer

Abstract: Intro Suppressing both androgens and estrogens may circumvent hormone receptor resistance in breast cancer by reducing androgen receptor stimulation. Selective inhibition of the 17, 20-lyase enzyme by orteronel leads to decreased androgen production in men and would be anticipated to reduce estrogen and androgen production in women. Thus, we conducted a phase 1b study of orteronel in postmenopausal women with hormone-receptor positive (HR+) metastatic breast cancer. Methods The primary objective was to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…In breast cancer, there are currently phase I and II clinical trials assessing the use of orteronel in patients with metastatic breast cancers that express AR (NCT01808040, NCT01990209). NCT01808040 assesses the safety of orteronel use for the treatment of postmenopausal women with hormone receptor positive metastatic breast cancer in addition to measuring the estradiol levels in these patients following treatment 153 . NCT01990209 is a phase II trial for male or female patients with metastatic AR+ BC (TNBC or ER+ and/or PR+ BC) with primary outcome measures of response and disease control rates.…”
Section: Cyp17-lyase Inhibitorsmentioning
confidence: 99%
“…In breast cancer, there are currently phase I and II clinical trials assessing the use of orteronel in patients with metastatic breast cancers that express AR (NCT01808040, NCT01990209). NCT01808040 assesses the safety of orteronel use for the treatment of postmenopausal women with hormone receptor positive metastatic breast cancer in addition to measuring the estradiol levels in these patients following treatment 153 . NCT01990209 is a phase II trial for male or female patients with metastatic AR+ BC (TNBC or ER+ and/or PR+ BC) with primary outcome measures of response and disease control rates.…”
Section: Cyp17-lyase Inhibitorsmentioning
confidence: 99%
“…An early phase 1b clinical trial showed that orteronel was well tolerated in postmenopausal women with HR+ metastatic breast cancer [9]. Of a cohort of eight heavily pretreated patients, a clinical benefit was seen in two patients who had a stable disease for more than 6 months.…”
Section: Co-targeting Ar and Cyp17 Lyasementioning
confidence: 99%
“…Many studies have sought its effects specifically in castration-resistant prostate cancer to improve overall survival [6][7][8]. New trials are aiming to apply this mechanistic effect on breast cancer patients, specifically using drugs that inhibit androgens via the CYP17 lyase pathway [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…2 The androgen receptor (AR) plays a crucial role in both prostate and breast cancers, though with distinct implications. 3 In aggressive prostate cancer, the AR emerges as a pivotal therapeutic target, and the administration of androgen receptor antagonists has already shown positive outcomes. 4 In breast cancer, particularly in the androgen receptor-positive (AR + ) subtype, ongoing research and clinical trials are exploring the potential of AR antagonists, 5 indicating a potential avenue for targeted therapy.…”
mentioning
confidence: 99%